Exogenous Application of Salicylic Acid and Hydrogen Peroxide Ameliorate Cadmium Stress in Milk Thistle by Enhancing Morpho-Physiological Attributes Grown at Two Different Altitudes - Nizar, Mereen; Shaukat, Kanval; Zahra, Noreen; Hafeez, Muhammad Bilal; Raza, Ali; Samad, Abdul; Ali, Qasim; Siddiqui, Manzer H.; Ali, Hayssam M. (Frontiers in Plant Science, 2022)
Cadmium (Cd+2) is a potential and widespread toxic environmental pollutant, mainly derived from a rapid industrial process that have inhibitory effects on growth, physiological and biochemical attributes of various plant species, including medicinal plants such as milk thistle. Plant signaling molecules, when applied exogenously, helps to enhance/activate endogenous biosynthesis of potentially important signaling molecules and antioxidants that boosts tolerance against various abiotic stresses, e.g., heavy metal stress. The present study documented the protective role of salicylic acid (SA; 0.25 µM) and hydrogen peroxide (H2O2; 10 µM) priming, foliar spray, and combinational treatments in reducing Cd+2 toxicity (500 µM) in milk thistle grown at two diverse ecological zones of Balochistan Province of Pakistan such as Quetta (Qta) and Turbat (Tbt). The morpho-physiological and biochemical attributes of milk thistle were significantly affected by Cd+2 toxicity; however, priming and foliar spray of SA and H2O2 significantly improved the growth attributes (root/shoot length, leaf area, root/shoot fresh and dry weight), photosynthetic pigments (Chl a, b and carotenoids) and secondary metabolites (Anthocyanin, Soluble phenolics and Tannins) at both altitudes by suppressing the negative role of Cd+2. However, the oxidative damage parameters, i.e., MDA and H2O2, decreased astonishingly under the treatment of signaling molecules, thereby protecting membrane integrity. The morphological variations were significant at the low altitude (Tbt) as compared to the high altitude (Qta). Interestingly, the physiological and biochemical attributes at both altitudes improved under SA and H2O2 treatments, thus hampered the toxic effect of Cd+2. These signaling compounds enhanced the defensive role of plants under heavy metal stress conditions with the consideration of altitudinal and ambient temperature variations remain to be the key concerns.